Perbedaan Status Gizi, PHBS, Gejala Skabies dan Suspek TBC pada Santri Pesantren Tradisional dan Pesantren Modern di Jawa Timur - Dwi Handayani; Kuuni Ulfah Naila El Muna; Mursyidul Ibad; Eva Komalasari; Sulfa Seti (ARTERI : Jurnal Ilmu Kesehatan, 2025)
The annual increase in the number of students from diverse backgrounds in Islamic boarding schools is inevitable. Generally, pesantren are categorized into two types: traditional (salafi) and modern (khalafi). These differences extend beyond the learning system to facilities and access to external environments, which may influence students’ health. This study aimed to analyze differences in health problems (nutritional status, clean and healthy living behavior/PHBS, symptoms of scabies, and suspected tuberculosis) among students in traditional and modern pesantren. This research employed an analytical observational design with a cross-sectional approach. The study population comprised students from two modern pesantren (An-Nur and Al-Jihad) and two traditional pesantren (Adurriyah and Darul Ubudiyah Raudlatul Muta’alimin). A purposive sampling technique was applied, yielding 154 participants, consisting of 78 students from modern pesantren and 76 students from traditional pesantren. Data were collected through interviews and anthropometric measurements to assess nutritional status. Bivariate analysis was performed to identify differences in health problems between the two types of pesantren, using chi-square and Mann-Whitney tests. Results showed that students in traditional pesantren were 15.6 times more likely to be suspected of tuberculosis compared to those in modern pesantren (OR 15.6). The proportion of undernutrition was 25% in traditional pesantren and 23.1% in modern pesantren. The mean PHBS score was higher in modern pesantren (8.94) compared to traditional pesantren (7.37). These findings highlight the need for strengthened health education, regular medical check-ups, and improved sanitation facilities in pesantren.